1970
DOI: 10.3126/kumj.v7i1.1764
|View full text |Cite
|
Sign up to set email alerts
|

Causes of vision impairment and assessment of need for low vision services for students of blind schools in Nepal

Abstract: Background: The present study is ¿ rst of its kind to evaluate causes of visual impairment of blind students in Nepal and assess their need for low vision rehabilitation services. Aim: To evaluate causes of vision impairment of students enrolled in blind schools in Nepal and assess the need for low vision rehabilitation services in these students. Materials and methods: A survey was conducted in 12 blind schools in Nepal, which were registered with Nepal Association for Welfare of Blindness (NAWB).It was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 2 publications
6
32
0
Order By: Relevance
“…In developing countries, blindness and SVI were due to avoidable causes like poor nutrition and lack of timely treatment. 2,[17][18][19][20][21] By comparison, in industrialised countries, they were mainly due to retinal, optic nerve diseases and birth defects. [22][23][24] A study in Iran showed an unusually high rate (81%) of SVI among children studying in schools for the blind and suggested that half of these cases were due to retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, blindness and SVI were due to avoidable causes like poor nutrition and lack of timely treatment. 2,[17][18][19][20][21] By comparison, in industrialised countries, they were mainly due to retinal, optic nerve diseases and birth defects. [22][23][24] A study in Iran showed an unusually high rate (81%) of SVI among children studying in schools for the blind and suggested that half of these cases were due to retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] A large number of children with low vision also study in these schools, either due to lack of facilities for low vision care, or to lack of awareness regarding integrated education for those with low vision disability. Often these children are only assessed at the time of admission and not subsequently revaluated.…”
mentioning
confidence: 99%
“…According to Nepal Blindness Study 1981, nutritional causes accounted for 17.9% of childhood blindness (Brilliant GE, 1988). A study shows 15.44% of the children blind or visually impaired due to nutritional factors (Kansakar I et al, 2009). No case of trachoma (active or inactive) presented to our OPD.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, another study conducted in the schools for blind and visually imapaired reported that 64.1% of children were blind due to avoidable causes, out of which 48.07% were preventable and 16.14% were treatable. Almost 36% of the students were blind because of the corneal cause (Kansakar I et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation